2021
DOI: 10.1136/bmjopen-2021-051574
|View full text |Cite
|
Sign up to set email alerts
|

Impact of school closures on the health and well-being of primary school children in Wales UK: a routine data linkage study using the HAPPEN Survey (2018–2020)

Abstract: ObjectivesThis study aimed to explore the relationship between initial school closures and children’s health by comparing health and well-being outcomes collected during school closures (April–June 2020) via HAPPEN (the Health and Attainment of Pupils in a Primary Education Network) with data from the same period in 2019 and 2018 via the HAPPEN Survey.SettingThe study was conducted online with 161 primary schools across Wales involved in the ‘HAPPEN At Home’ Survey.ParticipantsData were collected via the ‘HAPP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 28 publications
(26 reference statements)
1
30
0
2
Order By: Relevance
“…The longer term risks to children’s mental health must also be considered as evidence has highlighted associations between loneliness and episodes of depression, with worse outcomes in scenarios of forced isolation such as school closures and quarantine measures [ 58 ]. Much of this research however, is based on parent or staff perceptions of how children’s health has been affected and it will also be important to consider research regarding objective measures and accounts from children themselves [ 59 – 61 ]. Furthermore, for children’s mental health to be considered a key priority within education provision as highlighted in recommendations in this study and advocated for by UNICEF [ 62 ], this must also be reflected within wider education and public health policy and investment.…”
Section: Discussionmentioning
confidence: 99%
“…The longer term risks to children’s mental health must also be considered as evidence has highlighted associations between loneliness and episodes of depression, with worse outcomes in scenarios of forced isolation such as school closures and quarantine measures [ 58 ]. Much of this research however, is based on parent or staff perceptions of how children’s health has been affected and it will also be important to consider research regarding objective measures and accounts from children themselves [ 59 – 61 ]. Furthermore, for children’s mental health to be considered a key priority within education provision as highlighted in recommendations in this study and advocated for by UNICEF [ 62 ], this must also be reflected within wider education and public health policy and investment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by HAPPEN on self-reported health behaviour measures from the first lockdown (April–June 2020) from children (aged 8–11) showed that children, as a group, were actually more physically active [ 36 ]. Whilst this provides a contrasting narrative, those on free school meals (used as a proxy for deprivation) who reported being less physically active.…”
Section: Discussionmentioning
confidence: 99%
“…This has impacted on their education and health-related behaviours such as nutrition and physical activity[2]. While a growing body of literature suggests children display fewer clinical symptoms[3], the COVID-19 pandemic has contributed to widened inequalities in children’s health, wellbeing and education[4,5]. Positive SARS-CoV-2 tests require periods of self-isolation, impacting children’s physical health and wellbeing, limiting opportunities for children to engage in health-promoting behaviours such as regular physical activity[6].…”
Section: Introductionmentioning
confidence: 99%
“…This has impacted on their education and healthrelated behaviours such as nutrition and physical activity [2]. While a growing body of literature suggests children display fewer clinical symptoms [3], the COVID-19 pandemic has contributed to widened inequalities in children's health, wellbeing and education [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation